Evaluation of immune responses to Brucella vaccines in mouse models: A systematic review - Darbandi, Atieh; Alamdary, Shabnam Zeighamy; Koupaei, Maryam; Ghanavati, Roya; Heidary, Mohsen; Talebi, Malihe (Frontiers in Veterinary Science, 2022)
Introduction: Despite the accessibility of several live attenuated vaccines for animals, currently, there is no licensed vaccine for brucellosis in human populations. Available and confirmed animal vaccines may be harmful and considered inappropriate for humans. Thus, human vaccines for brucellosis are required. We aimed to evaluate the effects of Brucella vaccines on mouse models and discuss the potential mechanisms of these vaccines for the design of the appropriate human vaccines. Materials and methods: A systematic search was carried out in Web of Science, Embase, and PubMed/Medline databases. The following MeSH terms were applied: brucellosis, vaccine, Brucella, and vaccination. The original manuscripts describing the Brucella vaccines on mouse models were included. The review articles, editorials, correspondences, case reports, case series, duplicate publications, and articles with insufficient data were excluded. Results: Of the 163 full texts that were screened, 17 articles reached to inclusion criteria. Pooling data from these trials showed significant protective efficacy of used vaccines, attenuation of spleen weight, and maximum levels of antibody classes in vaccinated animals compared with animals challenged with different virulent strains of Brucella. And also, this review highlights developing a live human vaccine based on the B. melitensis as the most common species of Brucella, should be considered. Conclusion: Brucella is responsible for half-million new cases globally annually, and the lack of a proper human vaccine poses the risk of brucellosis. A variety of vaccines are used to prevent brucellosis. Subunit vaccines and recombinant human vaccines have higher safety and protective properties. Although vaccination helps brucellosis control, it does not eradicate the disease. Thus, we recommend the following strategies. A) establishment of a registration system; b) close monitoring of slaughterhouses, markets, and herds; c) training veterinarians; d) legal protection of the consequences of non-compliance with preventive measures.